Investigation of key metrics in freestyle swimming at different effort levels and breathing sides - Stamm, A.; Shlyonsky, I. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION MEMS sensors (IMU`s) are widely available nowadays and tend to be used more often in swimming in the past years (Guignard, Rouard, Chollet, & Seifert, 2017). These sensors have very good measurement capabilities today, but the automatic analysis of the gathered data has not yet been implemented. Our objective is to develop and validate an automatic analysis which can provide the swimmers/coaches with nearly immediate feedback on a smartphone/tablet.